The Quality of Life of Residents of a Satellite Degraded City District as Part of Urban Development Policy - Szafranek, Edyta (European Spatial Research and Policy, 2017)
The purpose of this article is to assess the quality of life of the residents of a degraded satellite area of a city. It is considered in the context of urban development policy – as the result of decisions and as a challenge for long-term development. The research was based on a case study, which is the district of Opole referred to as Metalchem. It is characterized by an isolated location in the city structure as well as economic transformations. The study was based primarily on an analysis of source materials and results of a survey. The results show that the assessment of the quality of life is inconsistent. The living conditions are good, but satisfactory fulfilment of social needs is lacking. The residents of the studied area feel that their quality of life is lower than that of other residents of the city. This situation is the result of three main factors: insufficient access to public services, an ingrained negative image of the quarter, and a lack of coherence and continuity of the policy regarding this area. Research shows that the quality of life of the residents of degraded and satellite districts depends on the management and investments in the area, on the area’s perceived status within the city, but primarily on a consistent implementation of spatial and economic policies. Ensuring cohesion and integration between the satellite districts and the city center as well as other districts is also important.